Application of nanoscale ZnS/TiO2 composite for optimized photocatalytic decolorization of a textile dye - Talebi, Sajad; Chaibakhsh, Naz; Moradi-Shoeili, Zeinab (Journal of applied research and technology, 2017)
•Nanoscale ZnS/TiO2 composite was synthesized and characterized.•The prepared photocatalyst was used for the removal of Acid Blue 113 dye.•The process was optimized and analyzed using central composite design.•A high AB113 dye removal (99.0%) was obtained at the optimal conditions. The synthesis of ZnS/TiO2 nanocomposite was successfully performed by a chemical deposition method. The structure and morphology of the prepared catalyst were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray (EDX), and FT-IR spectroscopy. The activity of the photocatalyst was evaluated for the removal of Acid Blue 113 (AB113) dye in aqueous solution under UV-A radiation. Response surface methodology (RSM) based on the central composite rotatable design (CCRD) was applied to study and optimize the photodegradation process. The effects of three experimental parameters including pH, irradiation time, and the catalyst dose on the AB113 removal were studied. A high dye removal (99.0%) was obtained by using minimum amount of the catalyst (37mg) at the optimal conditions of 27.32min and pH 6.18. Compared with pure nano-sized TiO2 and ZnS, the synthesized nanocomposite exhibited a higher photocatalytic activity. The kinetics of AB113 adsorption on the surface of ZnS/TiO2 nanocomposite could be described by the pseudo second order and parabolic-diffusion models.